Impact of a pharmacy-led screening and intervention in people at risk of or living with chronic kidney disease in a primary care setting: a cluster randomised trial protocol - Natasa Gisev; Sanjyot Vagholkar; Kamal Sud; Judy Mullan; Ines Krass; Anh Tran; Rita McMorrow; Wubshet Tesfaye; David W. Johnson; Connie Van; Vincent L. Versace; Judith Fethney; et al. (BMJ Open)
Introduction Chronic kidney disease (CKD) is increasingly recognised as a growing global public health problem. Early detection and management can significantly reduce the loss of kidney function. The proposed trial aims to evaluate the impact of a community pharmacy-led intervention combining CKD screening and medication review on CKD detection and quality use of medicines (QUM) for patients with CKD. We hypothesise that the proposed intervention will enhance detection of newly diagnosed CKD cases and reduce potentially inappropriate medications use by people at risk of or living with CKD.Methods and analysis This study is a multicentre, pragmatic, two-level cluster randomised controlled trial which will be conducted across different regions in Australia. Clusters of community pharmacies from geographical groups of co-located postcodes will be randomised. The project will be conducted in 122 community pharmacies distributed across metropolitan and rural areas. The trial consists of two arms: (1) Control Group: a risk assessment using the QKidney CKD risk assessment tool, and (2) Intervention Group: a risk assessment using the QKidney CKD plus Point-of-Care Testing for kidney function markers (serum creatinine and estimated glomerular filtration rate), followed by a QUM service. The primary outcomes of the study are the proportion of patients newly diagnosed with CKD at the end of the study period (12 months); and rates of changes in the number of medications considered problematic in kidney disease (number of medications prescribed at inappropriate doses based on kidney function and/or number of nephrotoxic medications) over the same period. Secondary outcomes include proportion of people on potentially inappropriate medications, types of recommendations provided by the pharmacist (and acceptance rate by general practitioners), proportion of people who were screened, referred, and took up the referral to visit their general practitioners, and economic and other patient-centred outcomes.Ethics and dissemination The trial protocol has been approved by the Human Research Ethics Committee at the University of Sydney (2022/044) and the findings of the study will be presented at scientific conferences and published in peer-reviewed journal(s).Trial registration number Australian New Zealand Clinical Trials Registry (ACTRN12622000329763).